Predicting the role of β-GAL genes in bean under abiotic stress and genome-wide characterization of β-GAL gene family members - Buttanri, Azize; Kasapoğlu, Ayşe Gül; Öner, Burak Muhammed; Aygören, Ahmed Sidar; Muslu, Selman; İlhan, Emre; Yildirim, Ertan; Aydin, Murat (Protoplasma, 2025)
Β -Gal s are a subgroup of the glycoside hydrolase (GH) family of enzymes, which possess the Glyco_hydro_35 (GH35) domain. Although studies have been conducted on the β-Gal gene family in numerous plant species, no such research has been conducted on beans. The purpose of this study was to determine the gene expression levels of β-Gal genes in the leaf tissue of P. vulgaris under salt and drought stress using quantitative real-time polymerase chain reaction (qRT-PCR) and to perform a comprehensive analysis of β-Gal gene family members using bioinformatics tools. In the bean genome, 25 Pvul-βGAL proteins with amino acid numbers ranging from 291 to 1119, molecular weights from 32.94 to 126.56 kDa, and isoelectric points from 5.46 to 9.08 were identified. Both segmental and tandem duplication have occurred in β-Gal genes in the bean genome, and Pvul-BGAL genes have been subject to negative selection in the evolutionary process. For a deeper comprehension of the evolutionary proximity of Pvul-BGAL genes, a phylogenetic tree and synteny map were drawn together with Arabidopsis thaliana and Glycine max β-Gal genes. The expression profiles of β-Gal genes in different tissues of the bean were determined in silico. In addition, the expression profiles of β-Gal genes in the leaves of bean plants subjected to drought and salt stress were analyzed, and the role of β-Gal genes in salt and drought stress was estimated. In this study, the role of β-Gal gene family in abiotic stress response and the characterization of β-Gal genes in beans were determined for the first time and will provide a basis for future functional genomics studies.